Insights Into MicroRNA-Mediated Regulation of Flowering Time in Cotton Through Small RNA Sequencing - Zhou, Yu; Myat, Aye Aye; Liang, Chengzhen; Meng, Zhigang; Guo, Sandui; Wei, Yunxiao; Sun, Guoqing; Wang, Yuan; Zhang, Rui (Frontiers in Plant Science, 2022)
The timing of flowering is a key determinant for plant reproductive success. It has been demonstrated that microRNAs (miRNAs) play an important role in the transition from the vegetative to the reproductive stage in cotton; however, knowledge remains limited about the regulatory role of miRNAs involved in flowering time regulation in cotton. To elucidate the molecular basis of miRNAs in response to flowering time in cotton, we performed high-throughput small RNA-sequencing at the fifth true-leaf stage. We identified 62 and 49 miRNAs that were significantly up- or down-regulated in two elite early flowering cultivars (EFC) compared with two late flowering cultivars (LFC), respectively. We next determined the expression profiles of the miRNA targets by RNA-sequencing analysis, and found that transcription of an SBP family transcription factor gene, GhSPL4, the target of GhmiR156, was significantly up-regulated in EFCs. Weighted gene co-expression network analysis (WGCNA) showed that GhSOC1, GhAP1, GhFD, GhCOL3, and GhAGL16 act as node genes in the auxin- and gibberellin-mediated flowering time regulatory networks in cotton. Elucidation of the miRNA-mediated flowering time regulatory network will contribute to our understanding of the molecular mechanisms underlying flowering time in cotton and cultivation of early-maturing cotton varieties.